Effect of Kiwi Fruit (Actinidia deliciosa) Extract on Histological Structure and Testicular Weight in Monosodium Glutamate-Induced Male Rats - Desti Asihanti Saputra; Devy Ariany; Lucky Brilliantina; Luluk Hermawati; Kamalia Layal (International Journal of Medicine and Health, 2026)
Monosodium glutamate (MSG) is a widely consumed food additive that has been reported to increase the production of reactive oxygen species (ROS), potentially inducing damage to various organs, including the testes. Oxidative stress in the testes may impair histological structure and disrupt the process of spermatogenesis. Antioxidants have been shown to attenuate the harmful effects of free radicals, and kiwifruit (Actinidia deliciosa) is recognized as a rich source of natural antioxidants. This study aimed to evaluate the effect of kiwifruit extract on testicular weight and histopathological characteristics in male Sprague Dawley rats exposed to MSG for 30 days. This experimental study used 25 male Sprague Dawley rats randomly assigned into five groups (n = 5 per group): negative control (K−), positive control receiving MSG at 4.8 g/kg body weight/day (K+), MSG plus vitamin C at 0.2 g/kg body weight/day (P1), MSG plus kiwifruit extract at 0.2 g/kg body weight/day (P2), and MSG plus kiwifruit extract at 0.4 g/kg body weight/day (P3). All treatments were administered for 30 consecutive days. Histopathological evaluation of the testes was performed on hematoxylin and eosin (H&E)-stained sections to assess the seminiferous tubule germinal epithelium, while testicular weight was measured at the end of the experiment. Data were presented descriptively as mean ± standard deviation. Histopathological examination demonstrated improved seminiferous tubule germinal epithelium in the P2 and P3 groups compared with the MSG-treated group (K+). The lowest mean testicular weight was observed in the P3 group (0.66 ± 0.31 g), compared with the K+ group (1.07 ± 0.28 g) and the negative control group (0.95 ± 0.30 g). Administration of kiwifruit extract tended to improve the histopathological appearance of the testes in male rats exposed to MSG, particularly in the P3 group, suggesting a potential protective effect against oxidative stress-induced testicular damage. However, the findings regarding changes in testicular weight remain descriptive and require confirmation through inferential statistical analysis.